(untitled) (Global Journal of Science Frontier Research, 2014)
Lead, Cadmium and Chromium concentration in spice samples collected from eastern Ethiopia were determined after digesting the samples by wet digestion methods using FAAS. Oven-dried 1 g spice samples were first Wet-digested in 8 ML of (69-70%) HNO3 and 2 ML of (30%) H2O2 for 3 hr at a temperature of 120 °C. Wet digestion method showed very fast, safer, simple and cleaner and also gives satisfactory recovery, detection limits and standard deviation relative to dry ashing method. Contents of investigated trace metal in spice samples of Lead in Fenugreek, Black cumin, garlic and ginger ranged from 0.0126 to 0.0155, 0.0205 to 0.0254, 0.0046 to 0.0066 and 0.0161 to 0.0178 mg/kg respectively. Cadmium is detected only in Fenugreek in the ranged of ND to 0.0175mg/kg where as Chromium in Fenugreek, Black cumin, Garlic and Ginger ranges from 0.0187 to 0.0219, 0.0134 to 0.0152, 0.0014 to 0.0016 and 0.0258 to 0.0346 mg/kg respectively.